The Performance Measures of Primary Health Care Quality: Experiences of Morocco Primary Health Centers during the ‘Quality Contest’ in 2010-2014 (41 Centers Audited) - B., Zaadoud; Y., Chbab; S., El Ghaza; A., Chaouch (European Scientific Journal, ESJ, 2017)
Objectives: The purpose of this article is to discuss the concept of performance measurement in primary health care through a framework called “Quality Contest (QC).” QC is used as a management tool and was implemented from 2007 to improve the quality of the Moroccan health care. The QC encompasses self-assessment, audit, feedback, and the development of improvement plan. Methodology: The audit peer listed 42 primary health care centers between 2010 and 2014 in four editions. The framework is a self-assessment guide which is made up of 42 items divided into 6 Domains. It was filled by the team of primary health center and a scoring guide for auditors including the expectation horizons. Results: This approach is one recommended in this process (CQ). Performance is evaluated according to the dimensions of the conceptual framework based on the stages of the Deming Cycle (Plan, Do, check, and improve). The overall average performance is 42 % with a minimum score of 17% and a maximum score of 88%. However, the poor performance is noted for the various dimensions: Customer Satisfaction (D1) 39%, Safety and Responsiveness (D4) 39%, and Partnership/Community Participation (D6) 39%. The performance according to the steps of the Deming wheel notes a decrease: step plan 61%, step Do 50%, step check 34%, and step improve 14%.